How Does AI-Powered CT Scan Analysis Work in Emergency Medicine? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Artificial intelligence (AI) is rapidly transforming medicine, particularly emergency medicine. In the high-stakes environment of an emergency department, ti...
Keywords: AI in Medical Imaging and Diagnostics; AI-Powered; Analysis; Emergency; Artificial Intelligence; Deep Learning